2005
DOI: 10.1152/ajpregu.00834.2004
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E at high doses improves survival, neurological performance, and brain mitochondrial function in aging male mice

Abstract: Male mice receiving vitamin E (5.0 g alpha-tocopherol acetate/kg of food) from 28 wk of age showed a 40% increased median life span, from 61 +/- 4 wk to 85 +/- 4 wk, and 17% increased maximal life span, whereas female mice equally supplemented exhibited only 14% increased median life span. The alpha-tocopherol content of brain and liver was 2.5-times and 7-times increased in male mice, respectively. Vitamin E-supplemented male mice showed a better performance in the tight-rope (neuromuscular function) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
161
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(186 citation statements)
references
References 48 publications
(74 reference statements)
15
161
2
Order By: Relevance
“…Many studies have suggested a mechanistic link between mtDNA mutations, a loss of mitochondrial respiratory enzyme functions, and generation of ROS from the mitochondria. A decreased electron transfer activity has been observed in the mitochondria of experimental animals on aging (Navarro et al, 2005;Mao et al, 2006). The activity of complexes I and IV in the mitochondrial fractions prepared from the brain tissue specimens of the aged WT mice were significantly lower compared with the young WT mice, whereas those of complexes II and III were unaffected (Fig.…”
Section: Inhibitory Effect Of Tfam Overexpression On Rotenoneinduced mentioning
confidence: 84%
See 1 more Smart Citation
“…Many studies have suggested a mechanistic link between mtDNA mutations, a loss of mitochondrial respiratory enzyme functions, and generation of ROS from the mitochondria. A decreased electron transfer activity has been observed in the mitochondria of experimental animals on aging (Navarro et al, 2005;Mao et al, 2006). The activity of complexes I and IV in the mitochondrial fractions prepared from the brain tissue specimens of the aged WT mice were significantly lower compared with the young WT mice, whereas those of complexes II and III were unaffected (Fig.…”
Section: Inhibitory Effect Of Tfam Overexpression On Rotenoneinduced mentioning
confidence: 84%
“…Behavioral dysfunctions associated with aging are also postulated to be associated with a decreased activity of mitochondrial electron transfer complexes with aging (Navarro et al, 2004(Navarro et al, , 2005. Furthermore, increased intracellular reactive oxygen species (ROS) activate microglia, which are representative resident mononuclear phagocyte populations in the brain, to induce an increased production of inflammatory mediators (Pawate et al, 2004;Qin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…9 Dietary supplementation with ␣-tocopherol increased significantly the median and maximum (oldest 10%) life span of mice in this study housed at 7 Ϯ 2°C, in accord with previous studies that maintained mice at more benign temperatures. 18,19,21,46 We initiated supplementation at 4 months of age, and the age of initiation and duration of supplementation may be critical in achieving positive life span effects, 19 with studies observing a life span extension generally starting vitamin E/␣-tocopherol supplementation earlier 18,19,46 rather than later in life. 14,24,47 The oxidative stress theory of aging suggests that damage to proteins, lipids, and DNA are a causal factor in the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…Using a comparative approach, Zou et al 17 reported that ␥-tocopherol, but not ␣-tocopherol, extended life span in Caenorhabditis elegans, but that neither isoform had any life span effect in Drosophila melanogastor or Anastrepha ludens. An increase in median/mean life span has been reported in various strains of mice following vitamin E supplementation [18][19][20][21] or following supplementation with a mixed antioxidant diet containing vitamins E and C. 22 However, other studies report no effect on life span or on oxidative stress following vitamin E supplementation or when using a mixed antioxidant diet. 14,23,24 There are several potential reasons why dietary antioxidants, such as vitamin E, have not become robust and repeatable pro-longevity treatments.…”
Section: Introduction Imentioning
confidence: 99%
“…There is an ongoing debate concerning the magnitude of decline in mitochondrial respiration that occurs during normal aging (Gilmer et al, 2010). Some groups report extensive age-related declines in mitochondrial respiration (Chiu and Richardson, 1980;Cocco et al, 2005;Navarro et al, 2005Navarro et al, , 2008Petrosillo et al, 2008a,b). Our laboratory and others (Bustamante et al, 2008;Deshmukh et al, 1980;Gilmer et al, 2010;Leslie et al, 1985;Meng et al, 2007) previously reported no significant age-related changes in cortical mitochondrial bioenergetics in naïve rats, while significant elevations in oxidative damage were apparent (Gilmer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%